2013
DOI: 10.2174/1386207311316060006
|View full text |Cite
|
Sign up to set email alerts
|

Ball Milling Synthesis of Silica Nanoparticle from Rice Husk Ash for Drug Delivery Application

Abstract: Silica nanoparticles were synthesized from rice husk ash at room temperature by using high energy planetary ball mill. The milling time and mill rotational speed were varied in four levels. The morphology of the synthesized powders was investigated by the FE-SEM and TEM image as well as XRD patterns. The results have revealed that the nano-sized amorphous silica particles are formed after about 6 h ball milling and they are spherical in shape. The average particle size of the silica powders is found to be arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…For more general sustainable NP manufacturing, natural plant materials such as English ivy, certain native plants from India, the traditional Chinese herb Cuscuta chinensis, glycyrrhizic acid from radix glycyrrhizae, guar gum, and rice husk also can also release their own organic nanoparticles of various sizes under appropriate conditions (Barve and Chaughule, 2013; Burris et al, 2012;Im et al, 2011;Lenaghan et al, 2013;Salavati-Niasari et al, 2012;Soumya et al, 2010;Wang et al, 2013;Yen et al, 2008). Beyond plant sources, a combination of ball-milling and ultrasound can reduce other organic material sources such as waste eggshells into calcium carbonate nanoparticles (Hassan et al, 2013).…”
Section: R Bell and Othersmentioning
confidence: 99%
“…For more general sustainable NP manufacturing, natural plant materials such as English ivy, certain native plants from India, the traditional Chinese herb Cuscuta chinensis, glycyrrhizic acid from radix glycyrrhizae, guar gum, and rice husk also can also release their own organic nanoparticles of various sizes under appropriate conditions (Barve and Chaughule, 2013; Burris et al, 2012;Im et al, 2011;Lenaghan et al, 2013;Salavati-Niasari et al, 2012;Soumya et al, 2010;Wang et al, 2013;Yen et al, 2008). Beyond plant sources, a combination of ball-milling and ultrasound can reduce other organic material sources such as waste eggshells into calcium carbonate nanoparticles (Hassan et al, 2013).…”
Section: R Bell and Othersmentioning
confidence: 99%
“…Porous silica nanoparticles with a diameter of ~70–75 nm was synthesized using ball‐milling method. Diameter size depends upon the rotational speed and milling times.This showed that a nanoporous silica carrier delayed the release of penicillin G. This can be beneficial for the controlled release of drugs 261. Amorphous silica‐based porous bioactive ceramics were prepared successfully by a gel‐casting method using silica xerogels powder derived from RHA.…”
Section: Second Generation Agricultural Wastes and Their Usesmentioning
confidence: 99%
“…85 Nanotechnologists have reported that ball milling generates NPs from rice husk ash. 81 Ball milling of eggshells, combined with ultrasound, makes calcium carbonate nanoparticles (cf., Calcarea Carbonica) Figure 1 Relationship between synthetic identity, biological identity, and physiological response. Synthetic identity is the size, shape, and surface chemistry of a nanomaterial post-synthesis.…”
Section: Homeopathic Manufacturingas Nanotechnology: Top-down and Botmentioning
confidence: 99%
“…79 These nanotechnology processes are respectively analogous to homeopathic manual trituration in dry lactose or succussions in liquid solutions. 79,81,86 One nanotechnology group found that combining milling with ultrasound agitation of the solutions was most effective for creating and dispersing the resultant NPs compared with either method by itself. 87 Clearly the traditional methods of homeopathic manufacturing with triturating and succussing are not identical to the procedures of modern nanotechnology, but the mechanical processes of prolonged grinding and agitation in solution overlap.…”
Section: Figure 2 Top Down and Bottom Up Manufacturing Strategies Formentioning
confidence: 99%